2020
DOI: 10.18203/2320-6012.ijrms20204886
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in involvement of male spouse in family planning program in rural areas of Varanasi

Abstract: Background: Globally, men have not shared equally with women the responsibility for fertility regulation. While family planning efforts have been directed almost toward women, the lack of male involvement may also reflect the limited options available to men. Current methods for men are condom, withdrawal, or permanent, such as vasectomy. The success of family planning depends on the involvement of couples but this hardly happen especially in rural areas. It is the belief, though erroneously among most males t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 8 publications
(11 reference statements)
3
4
0
Order By: Relevance
“…Studies conducted by Wondum et al and Butto et al were showed almost similar findings. 13,21 Our study showed 59.4% of men encourage their spouse to use family planning and 54.5% of men support their spouse in family planning which were almost similar findings as study conducted by Wondum et al 13 It was also seen in present study that 42.9% of men approved their spouse for contraceptive use which was almost similar to a study conducted by Kassa et al 22 Regarding decision making in family planning, it was found that 54.5% of participants themselves, 30.9% participants with spouse, and 14.5% of participant's wife had taken such decisions, these findings were almost similar as study conducted by Sing et al 15 But it was discordant with the study conducted in Haryana by Walia et al 23 This difference may be due to gender difference in study population.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Studies conducted by Wondum et al and Butto et al were showed almost similar findings. 13,21 Our study showed 59.4% of men encourage their spouse to use family planning and 54.5% of men support their spouse in family planning which were almost similar findings as study conducted by Wondum et al 13 It was also seen in present study that 42.9% of men approved their spouse for contraceptive use which was almost similar to a study conducted by Kassa et al 22 Regarding decision making in family planning, it was found that 54.5% of participants themselves, 30.9% participants with spouse, and 14.5% of participant's wife had taken such decisions, these findings were almost similar as study conducted by Sing et al 15 But it was discordant with the study conducted in Haryana by Walia et al 23 This difference may be due to gender difference in study population.…”
Section: Discussionsupporting
confidence: 89%
“…If we see in our study only 25.6% of participants were using condoms. It was almost similar in studies conducted by Basu et al and Nasir et al 16,20 But it was quite small than the study conducted by Sing et al 15 Though we found participant's knowledge on male contraceptives was adequate but none of them were using vasectomy. NFHS-4 data from this district also showed no participation by male in vasectomy.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations